2014
DOI: 10.3389/fnbeh.2014.00299
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of amygdala activation with real-time fMRI neurofeedback in a healthy female sample

Abstract: Psychiatric conditions of emotion dysregulation are often characterized by difficulties in regulating the activity of limbic regions such as the amygdala. Real-time functional magnetic resonance imaging (rt-fMRI) allows to feedback brain activation and opens the possibility to establish a neurofeedback (NF) training of amygdala activation, e.g., for subjects suffering from emotion dysregulation. As a first step, we investigated whether feedback of the amygdala response to aversive scenes can improve down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 63 publications
11
103
0
1
Order By: Relevance
“…As shown in previous fMRI-NF studies (Sulzer et al, 2013a,b;Bruhl et al, 2014;Lawrence et al, 2014;Paret et al, 2014), we found that volitional regulation of localized limbic activity could be obtained even after one session. Interestingly, comparing the two NF trials conducted in session 1 (baseline vs. training I) revealed that, at this stage, no significant difference existed in the effect size facilitated by the AS relative to the TM (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…As shown in previous fMRI-NF studies (Sulzer et al, 2013a,b;Bruhl et al, 2014;Lawrence et al, 2014;Paret et al, 2014), we found that volitional regulation of localized limbic activity could be obtained even after one session. Interestingly, comparing the two NF trials conducted in session 1 (baseline vs. training I) revealed that, at this stage, no significant difference existed in the effect size facilitated by the AS relative to the TM (Figure 2).…”
Section: Discussionsupporting
confidence: 62%
“…For example, a yet-to-be-published rtfMRI-nf experiment, discussed in an authoritative review (Sulzer, Haller, et al, 2013), showed that participants who received explicit instructions for mental strategies, compared to individuals left to explore and develop them implicitly on their own, were more successful at neural self-regulation. Moreover, comparing veritable feedback with no feedback , inversely proportional feedback , or feedback from a distinct brain region (Paret et al, 2014), revealed similar neural changes from baseline to the first trial in both experimental and control groups. On the other hand, findings from both human and animal studies suggest that explicit techniques are unnecessary and that contingent feedback alone is responsible for neural regulation (Caria et al, 2010;Koralek, Jin, Long, Costa, & Carmena, 2012).…”
Section: Fmrimentioning
confidence: 78%
“…Whereas EEG-nf requires many sessions to alter electrical activity, with rtfMRI-nf individuals can selectively modify fMRI BOLD signal within 30 minutes of training and sometimes even sooner (Brühl et al, 2014;Canterberry et al, 2013;Greer, Trujillo, Glover, & Knutson, 2014;Gröne et al, 2015;Hui, Zhang, Ge, Yao, & Long, 2014;Lawrence et al, 2014;Paret et al, 2014;. This striking difference between EEG-nf and rtfMRI-nf deserves further discussion.…”
Section: Fmrimentioning
confidence: 99%
“…Ergo, participants are presented with online information that corresponds to their success in regulating the ROI. In support of this concept, selfregulation of the amygdala as compared with sham regions via rt-fMRI-nf has been shown to concomitantly affect activation in PFC areas involved in emotion regulation, as well as enhance amygdala-PFC connectivity [Koush et al, 2013;Paret et al, 2014;Zotev et al, 2011] and amygdalarostral ACC coupling [Zotev et al, 2011]. Several studies have examined the capacity to regulate emotions by targeting neurofeedback of the amygdala using rt-fMRI-nf, in healthy individuals [Br€ uhl et al, 2014;Keynan et al, 2016;Paret et al, 2014Paret et al, , 2016bZotev et al, 2011] as well as in psychiatric populations, including borderline personality disorder (BPD) [Paret et al, 2016a], and major depressive disorder [Young et al, 2014;Zotev et al, 2016].…”
Section: Introductionmentioning
confidence: 95%